Response of Natural Cyanobacteria and Algae Assemblages to a Nutrient Pulse and Elevated Temperature - Lürling, Miquel; Mello, Mariana Mendes e; van Oosterhout, Frank; de Senerpont Domis, Lisette; Marinho, Marcelo M. (Frontiers in Microbiology, 2018)
Eutrophication (nutrient over-enrichment) is the primary worldwide water quality issue often leading to nuisance cyanobacterial blooms. Climate change is predicted to cause further rise of cyanobacteria blooms as cyanobacteria can have a competitive advantage at elevated temperatures. We tested the hypothesis that simultaneous rise in nutrients and temperature will promote cyanobacteria more than a single increase in one of the two drivers. To this end, controlled experiments were run with seston from 39 different urban water bodies varying in trophic state from mesotrophic to hypertrophic. These experiments were carried out at two different temperatures, 20 °C (ambient) and 25 °C (warming scenario) with or without the addition of a surplus of nutrients (eutrophication scenario). To facilitate comparisons, we quantified the effect size of the different treatments, using cyanobacterial and algal chlorophyll a concentrations as a response variable. Cyanobacterial and algal chlorophyll a concentrations were determined with a PHYTO-PAM phytoplankton analyzer. Warming caused an 18% increase in cyanobacterial chlorophyll-a, while algal chlorophyll-a concentrations were on average 8% higher at 25ºC than at 20ºC. A nutrient pulse had a much stronger effect on chlorophyll-a concentrations than warming. Cyanobacterial chlorophyll-a concentrations in nutrient enriched incubations at 20ºC or 25ºC were similar and , but had been increased 900% compared9 times higher than to in the incubations at 20ºC without nutrient pulse. Likewise, algal chlorophyll-a concentrations increased by 600%were 6 times higher. The results of this study confirm that warming alone yields marginally highermore cyanobacteria chlorophyll-a concentrations, yet that a pulse of additional nutrients is boosting blooms. The responses of seston originating from mesotrophic waters seemed less strong than those from eutrophic waters, which indicates that nutrient control strategies –catchment as well as in-system measures– could increase the resilience of surface waters to the negative effects of climate change.